Inert and nitrated cross-linked β-cyclodextrin binders for energetic applications - Luppi, Federico (Cranfield University, 2019)
This PhD project focuses on the synthesis of new inert and nitrated cross-linked cyclodextrin systems as binders for energetic formulations. Three diglycidyl ethers with polyethylene glycol segments differing in length were used to crosslink β-cyclodextrin. The physicochemical properties of the compounds were investigated by proton nuclear magnetic resonance spectroscopy, differential scanning calorimetry, thermogravimetric analysis and dynamic mechanical analysis. The polyethylene glycol chains linked to the rigid β-cyclodextrin conferred low glass transition temperatures (≥ –20 °C) on the inert binders and also on their nitrated derivatives (≥ –14 °C). This is the first time that nitrated βcyclodextrin derivatives have shown viscoelastic behaviour at temperatures below 0 °C. The viscoelasticity of both the inert and nitrated compounds increased with the amount of polyethylene glycol chains in the system. Inert binders with higher polyethylene glycol:β-cyclodextrin units ratios were softer and exhibited self-healing behaviour. The thermo-mechanical characterisation of these binders revealed that the system was exposed to mechanical stress below the glass transition temperature, and the stress was directly related to the proportion of the soft polyethylene glycol segments. The nitrated cross-linked derivatives were characterised by decomposition temperatures of ~200 °C and thermal degradation energies of 1400–2100 J g -1 strictly dependent on the degree of cross-linking and nitration. Self-healing properties were confirmed in nitrated products with a high polyethylene glycol segments content. Nitrated samples with polyethylene glycol segments:β-cyclodextrin units ratios >3.8:1 were safer to handle in the laboratory as determined by small-scale hazard and compatibility tests with various energetic fillers. Additionally, preliminary Energetic Materials Testing Assessment Policy (EMTAP) tests confirmed the samples were not sensitive to electrostatic discharge up to 4.5 J but were sensitive to impact, with a figure of insensitiveness of 29. The nitrated samples were unstable at temperatures >80 °C. The materials developed during this PhD project could facilitate the manufacturing and storage of new binders and may offer a suitable replacement for nitrocellulose and other binders in ii energetic formulations. The stabilisation of the nitrated cross-linked binders should be prioritised in future work